Music Creation Tirta Pemutih | Kreasi Musik Tirta Pemutih - I Putu Nanda Yoga Mayura; Ni Ketut Dewi Yulianti; I Made Dwi Andika Putra (GHURNITA: Jurnal Seni Karawitan, 2022)
Tabuh kreasi Tirta Pemutih is a work created from the transformation of an object from a holy spring in the Pura Dalem Pemutih area. The uniqueness obtained such as water waves, the name of a temple where this object is located, and the duality of different water sources are the ideas in the creation of this work. The purpose of creating tabuh kreasi Tirta Pemutih is to transform the ideas obtained into a concept through the Balinese karawitan music. The creation of this work uses the method of creation from Alma M. Hawkins which includes the exploration stage, the improvisation stage, and the forming stage. From this method, the creator carries out a creative process to create tabuh kreasi Tirta Pemutih. The result of the creation process in tabuh kreasi Tirta Pemutih is that the creator is able to transform the ideas obtained from a holy spring into a tabuh kreasi entitled Tirta Pemutih. In essence, tabuh kreasi Tirta Pemutih is a medium to introduce a holy spring object to the listeners through concepts that have been created and presented in a dissemination.   Keywords: Holy Spring, Tabuh Kreasi, Tirta Pemutih